2014
DOI: 10.1001/jamadermatol.2013.7321
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Mobile Teledermatology in Human Immunodeficiency Virus–Positive Patients in Botswana

Abstract: Importance Mobile teledermatology may increase access to care. Objective To determine if mobile teledermatology in HIV positive patients in Gaborone, Botswana was reliable and produced valid consultations in comparison to face-to-face dermatology consultations. Design Cross-sectional study Setting Outpatient clinics and public inpatient settings in Botswana. Participants 76 HIV positive patients aged 18 years and up with a skin or mucosal complaint that had not been previously evaluated by a dermatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Each of the pilot projects focused on specific objectives and was evaluated based on the respective objectives as shown below: Cervical Cancer Screening: Evaluating the use of mobile phone telemedicine for cervical cancer screening ( 9 ). Teledermatology: Determining the reliability and validity of mobile teledermatology in HIV positive patients in a resource-limited setting ( 10 ). Teledermatology: Evaluating patients’ perception of mobile teledermatology ( 11 ).…”
Section: Pilot Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the pilot projects focused on specific objectives and was evaluated based on the respective objectives as shown below: Cervical Cancer Screening: Evaluating the use of mobile phone telemedicine for cervical cancer screening ( 9 ). Teledermatology: Determining the reliability and validity of mobile teledermatology in HIV positive patients in a resource-limited setting ( 10 ). Teledermatology: Evaluating patients’ perception of mobile teledermatology ( 11 ).…”
Section: Pilot Projectsmentioning
confidence: 99%
“…Teledermatology: Determining the reliability and validity of mobile teledermatology in HIV positive patients in a resource-limited setting ( 10 ).…”
Section: Pilot Projectsmentioning
confidence: 99%
“…Mobile teledermatology uses cell phones to transmit images, allows for more versatility than its often more unwieldy store-and-forward counterpart, and has good concordance with the outcomes of a face-to-face visit (3639). Teledermatology has been validated in both infectious conditions such as HIV-associated skin conditions and chronic conditions, such as atopic dermatitis (37,40). A cross-sectional survey of HIV positive patients in Botswana found that 91% of patients felt that a mobile teledermatology visit would provide the same level of care as a face-to-face visit (41).…”
Section: Improving Quality Of Care Through Innovationmentioning
confidence: 99%
“…Clinical services (telemedicine) have also taken place within Botswana. Most studies (18) have been performed by a single research group, the BUP Partnership [13,18,20,21,[26][27][28][33][34][35][36][37][38][39][40][41][42][43]. The available evidence suggests this partnership is no longer functional.…”
Section: Literature Findingsmentioning
confidence: 99%